CAPACITAÇÃO SOB A ÓTICA DA GOVERNANÇA COLABORATIVA: UMA ANÁLISE DO GRAU DE MATURIDADE DE UMA INSTITUIÇÃO PÚBLICA - dos Santos Souza, Plinio (LINKSCIENCEPLACE, 2026)
The research seeks to evaluate the degree of collaborative maturity of the training partnerships of a certain federal public institution. From this analysis, propose improvements in terms of governance for institutional capacity building. In methodological terms, the research is characterized as a unique case study of descriptive exploratory character. The theoretical model adopted was the Collaborative Governance Regime (RGC) of Emerson et. al. (2011). Data collection took place in two ways: application of the collaborative maturity instrument (MARTINS and RIBAS, 2017) and the performance of semi-structured interviewees. Ten training partnerships were evaluated, totaling twenty-three partners. The criterion for data collection in both cases was accessibility. In addition, two levels of analysis were used: for each selected partnership; general understanding of all selected partnerships. The results indicate a considerable degree of collaborative maturity, in general, in the selected partnerships. Evidence suggests a need for collaborative improvement in the following dimensions and variables: drivers (interdependence and uncertainty); engagement with principles (deliberation and determination); capacity of joint action (resources and institutional arrangements). It is recommended the appropriation of the concept of "colaborarquia" (AGRANOFF, 2007) and of collaborative platforms (ANSELL and GASH, 2018). The social contributions of the research are: enhancement and stimulation of collaborative actions in the Public Administration for interaction beyond the borders of public institutions. It is believed to be one of the first studies that seeks to evaluate collaborative maturity in terms of institutional capacity building in public institutions, from the perspective of Collaborative Governance.